Detection of bacterial soft-rot of crown imperial caused by Pectobacterium carotovorum subsp. carotovorum using specific PCR primers - E. Mahmoudi; M.J. Soleimani; M. Taghavi (Phytopathologia Mediterranea, 2007)
Pectobacterium is one of the major destructive causal agent in most crop plants throughout the world. During a survey in spring of 2005 in the rangeland of Kermanshah and Isfahan, provinces of Iran, samples of bulbs and stems of crown imperial with brown spot and soft rot were collected. Eight strains of pectolytic Erwinia were isolated and purified from these samples. Phenotypic tests indicated that the strains were gram-negative, facultative anaerobic, rod shaped, motile with peritrichous flagella. They were oxidase negative, catalase positive and also able to macerate potato slices. Pathogenicity of all the strains were confirmed on corn, philodendron and crown imperial by inoculation of these crops with a bacterial suspension and reisolation of the strain from symptomatic tissues. A pair of specific PCR primers was used to detect these bacterial strains. The primer set (EXPCCF/EXPCCR) amplified a single fragment of the expected size (0.55 kb) from genomic DNA of all strains used in this study. In nested PCR, the primer set (INPCCR/INPCCF) amplified the expected single fragment (0.4 kb) from the PCR product of first PCR amplification. On the basis of the biochemical and phenotypic characteristics and PCR amplification by the specific PCR primers, these strains were identified as Pectobacterium carotovorum subsp. carotovorum. This is the first report of occurrence of crown imperial bacterial soft-rot in Iran.